Управління міжнародними проектами у ВНЗ України - Брінь, Павло Володимирович; Мушинська, Г. В. (НТУ "ХПІ", 2014)
У статті розглядається міжнародна проектна діяльність у вищих навчальних закладах України. Досліджуються її становлення та розвиток впродовж часу, розглядаються особливості та виділяються загальні тенденції. Показано, що стихійне впровадження такого роду інновацій лише погіршує стан системи вищої освіти в цілому через актуалізацію різних ризиків. Пропонуються шляхи вирішення проблем в управлінні міжнародними проектами у вищих навчальних закладах України.

The article deals with the international project activity of the higher education institutions in Ukraine. The authors study the formation of the international project activities in Ukrainian HEIs, its development during the time, define its features and distinguish the common trends. The statistics of the projects implemented in Ukraine by universities is given. The universities participated in more projects are defined. The obstacles of the project activities development are studied. The key challenges and problems in the further implementation of the project activities are revised and the methods of their solving are proposed.
Management of the international projects in HEIs of Ukraine
Keywords: вищі навчальні заклади; глобалізація; інтеграція; інтернаціоналізація; міжнародний проект; проектна діяльність; higher education; globalization; integration; internationalization; international project; project activities